Ojcowie Kościoła w teologii anglikańskiej - Nowosad, Sławomir (Vox Patrum, 2023)
It is in the context of tradition that the Church of England in her major ecclesiastical and theological figures has endeavoured to perceive the Protestant principle of sola Scriptura. Hence, the Fathers of the Church became the “bright stars” to guide Christ’s disciples towards a better understanding of the word of God and towards a more authentic Christian life. Both the Book of Common Prayer and the 39 Articles not infrequently refer to the Fathers to prove the Church of England’s continuity with the early Church. T. Cranmer, R. Hooker and J. Jewel were among those who, against Puritan criticisms, saw as essential the Anglican faithfulness to Church Fathers. J. Cosin, J. Taylor or G. Bull followed their methodology to defend, for example, the episcopal character of the English Church. A new impulse for a return to the Catholic antiquity within the Church of England came from the Tractarians who produced the Library of the Fathers and thus struggled to revive the Catholic faith of their Church, her sacramental and liturgical life. The present-day theologians like, for example, F. L. Cross, R. Williams, S. Coakley, C. Harrison or A. Louth have been those whose fresh efforts attested, though always cautiously, to the ongoing Anglican interests in Christian antiquity. The focus of the final part of the paper is on Bishop K. E. Kirk, the 20-century most prominent figure in Anglican moral theology, whose extensive study in the early Church allowed to demonstrate comprehensively Christian moral life as aimed at visio Dei.